Long-term effect of corneoscleral contact lenses on refractory ocular surface diseases. Issue 4 (August 2019) - Lee, Sang-Mok; Kim, Yu Jeong; Choi, Se Hyun; Oh, Joo Youn; Kim, Mee Kum
Highlights: Smaller corneoscleral lenses are beneficial in shortened fornices, especially in Asians who have a small fissure. Corneoscleral lenses were successfully fitted in 10 out of 13 eyes with severe refractory ocular surface diseases. Fitting failed in three eyes due to small palpebral fissure/shortened fornices (two eyes) and handling difficulty. The well-fitted corneoscleral lenses demonstrated therapeutic benefits in severe refractory ocular surface diseases. Corneoscleral contact lenses can be an option for the management of severe refractory ocular surface diseases. Abstract: Purpose: To report the therapeutic effect of corneoscleral contact lenses (CLs) with a diameter of 14.0 mm on the refractory ocular surface diseases. Methods: Medical records of 13 eyes (of nine patients) attempted for fitting with corneoscleral CLs for the management of the severe refractory ocular surface diseases were retrospectively reviewed including Stevens-Johnson syndrome (SJS; eight eyes) and chronic ocular graft-versus-host disease (GVHD; five eyes). Lenses were fitted to improve refractory punctate epithelial erosions (PEE, ten eyes) and persistent epithelial defect (PED, three eyes with SJS) despite the proper medical management. Short-term (1 month) and long-term (12 months) changes in the best corrected visual acuity (BCVA), corneal fluorescein staining (CFS) score, mean wearing time, and National Eye Institute's Visual Function Questionnaire-25 (VFQ-25) were evaluated. Results: Of the 13 eyes, ten eyes were successfully fitted with the corneoscleral CLs. The fitting was failed in three eyes due to small palpebral fissure and shortened fornices (two eyes) and handling difficulty (one eye). At one-month follow-up after successful fitting in ten eyes, mean wearing time was 12.6 h (6.5–17, all day long) and BCVA improved from 0.56 ± 0.59 to 0.27 ± 0.46 in logMAR ( P  = .018). For the eight well-fitted eyes with refractory PEE, CFS score improved from 7.38±2.20 to 5.13±2.48 ( P  = .024). PED improved in all two eyes which were successfully fitted with corneoscleral CLs (Of the three eyes with PED, one eye failed fitting). At 12-month follow-up, mean wearing time was 11.4 h and the improved BCVA and CFS score were maintained. Furthermore, no adverse events attributable to corneoscleral CLs use occurred. Conclusion: The corneoscleral CLs with a diameter of 14.0 mm were successfully fitted in ten out of 13 eyes with severe refractory ocular surface diseases and demonstrated therapeutic benefits in the well-fitted eyes. The corneoscleral CL can be an option in the management of severe refractory ocular surface diseases.